Nothing spreads like technology: Digitalisation and its Interaction with Institutions and Governance - Labhard Vincent; Lehtimäki Jonne; Baccianti Claudio (SUERF - The European Money and Finance Forum, 2026)
The increase in digital technologies, goods, and services, commonly referred to as digitalisation, is one of the most important transformations in the history of humankind, affecting economies worldwide. This process of technology diffusion has profound effects and policy implications, but how widely and how intensively those technologies are used appears to depend on factors that are determined at the country level. The results of our analysis indicate that a higher quality of institutions is usually associated with both a greater speed of diffusion and a greater spread of digital technologies. The results also suggest that there are large, policy-relevant differences in the diffusion process depending on the level of development as well as the state of technological change of a country.